Multidisciplinary Team Approach for Morbidly Adherent Placenta: Maternal Outcomes Compared with Standard Care: Multidisciplinary Team Approach for Morbidly Adherent Placenta - Iftikhar, Bushra; Khan, Umber Imtiaz; Tariq, Amera; Nasreen, Samia; Anwar, Rabiah; Khan, Samina Rehan (Pakistan Journal of Health Sciences, 2026)
Morbidly adherent placenta (MAP), part of the placenta accreta spectrum, is a major cause of severe obstetric hemorrhage and may lead to massive transfusion, peripartum hysterectomy, ICU care, and maternal morbidity. Rising cesarean section rates are increasing the burden of MAP in Pakistan. Multidisciplinary team (MDT) management is proposed to improve preparedness, but outcome benefits remain uncertain. Objective: To compare maternal outcomes in patients with MAP managed by an MDT versus standard obstetric care. Methods: A comparative, non-randomized observational study was conducted at the Department of Obstetrics and Gynecology, Pakistan Navy Ship Shifa Hospital, Karachi, from February 2022 to July 2022, vide Ethical Committee PNS Shifa approval. A total of 151 women diagnosed with MAP were included. Outcomes included maternal morbidity, estimated blood loss (EBL), transfusion requirement, time to intervention, hospital stay, and surgical procedures. Results: Overall mean EBL was 512.24 mL, and mean transfusion requirement was 1.91 units. Compared with standard care, MDT management showed no significant differences in EBL (p=0.300), transfusion units (p=0.237), time to intervention (p=0.426), or hospital stay (p=0.926). Maternal morbidity and major surgical interventions were also comparable between groups. Conclusions: MDT-based care showed no significant improvement in blood loss, transfusion needs, or maternal morbidity compared with standard care.